2011
DOI: 10.1016/j.bbr.2011.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent perseveration correlates with abnormal repetitive locomotion in adult mink but is not reduced by environmental enrichment

Abstract: a b s t r a c tWe analysed the relationship between abnormal repetitive behaviour (ARB), the presence/absence of environmental enrichment, and two types of behavioural disinhibition in farmed American mink, Neovison vison. The first type, recurrent perseveration, the inappropriate repetition of already completed responses, was assessed using three indices of excessive response repetition and patterning in a biascorrected serial two-choice guessing task. The second type, disinhibition of prepotent responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 82 publications
1
39
0
Order By: Relevance
“…mink fed thiaminase-containing diets also did not observe central nervous system symptoms, although significant loss of appetite did occur and thiamine supplements were required, indicating thiaminase activity (Rouvinen et al 1997). Motivational or learning differences may account for mink that never completed the task, or that stopped making attempts later in the study as shown in other studies where some individual mink never completed the assigned task Dallaire et al 2011).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…mink fed thiaminase-containing diets also did not observe central nervous system symptoms, although significant loss of appetite did occur and thiamine supplements were required, indicating thiaminase activity (Rouvinen et al 1997). Motivational or learning differences may account for mink that never completed the task, or that stopped making attempts later in the study as shown in other studies where some individual mink never completed the assigned task Dallaire et al 2011).…”
Section: Discussionmentioning
confidence: 75%
“…Locomotor stereotypy, which might indicate neurological damage (Mason 2006), showed some variation between groups, but this was inconsistent across the first 5 wk, negating firm conclusions. Environmental enrichment provided to adult mink will decrease levels of stereotypic behaviors, possibly acting on neurological pathways (Dallaire et al 2011), but enrichment is more effective when provided at a younger age (Dallaire et al 2011). Therefore, it is possible that stronger effects would have been seen on the stereotypies of juveniles fed thiaminase-containing feedstuffs over adult mink on these diets.…”
Section: Discussionmentioning
confidence: 99%
“…First, unlike Locomotor SB, it often appears to be directed at other mink, and previous authors have reported that similar "scratching" seems to be an attempt to enter areas to which access is denied (nest box: Hansen and Jeppesen, 2000;mother: Houbak andJeppesen, 1987, cited in Akre et al, 2008). Second, unlike Locomotor SB, it does not correlate with recurrent perseveration (Dallaire et al, 2011). Third, unlike Locomotor SB, Scrabbling is not widely reported across captive Carnivora.…”
Section: Behavioural Observationsmentioning
confidence: 87%
“…Furthermore, two potential confounding variables are well understood in mink. We have previously shown that the first potential confound, perseveration, does not directly predict the response of SB to EE in mink (Dallaire et al, 2011), but more subtle effects are possible: highly perseverative subjects may still show reduced use of enrichments due to limited behavioural flexibility, potentially contributing to less effective SB reduction. We screened our mink for perseveration to test whether perseverative tendencies compromise EE use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation